The investigating of clinical and radiological findings of hepatic actinomycosis - Koc, Mustafa (My University, 2022)
Actinomycosis is a rare chronic suppurative granulomatous infection of the oropharynx, gastrointestinal, and urogenital tract. Infection most commonly manifests as a cervicofacial disease but less frequently in the thoracic and abdominopelvic region. Hepatic actinomycosis (HA) is rare and usually secondary to abdominal actinomyco- sis. It can mimic hepatic malignant tumors. There is not enough information in the literature about HA. In this study, radiological and clinical findings of HA cases were investigated. Between January 2013 and February 2021, a total of 12 patients diagnosed with HA were retrospectively analyzed. Significant clinical and laboratory findings and radiological findings related to current pathology were noted. The mean age of the patients ranged from 23 to 75 years (mean age, 52.2 years). There were 7 male and 5 female patients. 85% of these patients had fever, 67% anemia, and 53% weight loss. Peripheral blood leukocytes were increased in all patients. 8 of the patients (66%) had a secondary infection of HA in the lungs, and pelvis organs. Radiologically, they were mostly low-intensity changes (66%), making them easily misdiagnosed as metastatic cancer and primary liver cancer. 17% seen acute bacterial abscess-like changes. A few cases exhibited cystic mass-like changes. In 64% of the patients, a single lesion was found. The right lobe of the liver was the most common infection area. A definitive diagnosis was made by histopathological examination. The diagnosis of primary HA is difficult to diagnose because of the nonspecific clinical and radiological findings. Differential diagnoses should be made with diseases that include both benign and malignant conditions.
Keywords: Tıbbi Araştırmalar Deneysel; Genel ve Dahili Tıp; Patoloji